Asian affinities and disparities with modern architecture and the Philippine adaptation - Bulaong, Carmen Bettina S. (Espasyo : Journal of Philippine Architecture and Allied Arts, 2014)
Modern formulated its Architectural idiom from a most unlikely wellspring : Southeast Asia turned out to be a source of overflowing inspiration for western art and architecture, particularly, when Japan had re-opened its doors to trading with the West in the 19th century after more than two centuries of national isolation. It is from this influx transcultural architecture gestated. This is the architecture of a turn-of-the-century European concept that stemmed from the rapid advancement in technology and the search for a new style that signified modernity, progress and power. This is the architecture that a growing middle class society would espouse.